2020 IEEE International Symposium on Mixed and Augmented Reality (ISMAR) 2020
DOI: 10.1109/ismar50242.2020.00026
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Object Shape, Fidelity, Color, and Luminance on Depth Perception in Handheld Mobile Augmented Reality

Abstract: Depth perception of objects can greatly affect a user's experience of an augmented reality (AR) application. Many AR applications require depth matching of real and virtual objects and have the possibility to be influenced by depth cues. Color and luminance are depth cues that have been traditionally studied in two-dimensional (2D) objects. However, there is little research investigating how the properties of three-dimensional (3D) virtual objects interact with color and luminance to affect depth perception, d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 53 publications
0
41
0
Order By: Relevance
“…They found that the richer geometry cues provided by the icosahedron and apple positively influenced reaching and grasping behaviors. In a similar manner, Do et al [15] evaluated the effect of object color and luminance on objects of different shapes for depth judgments in mobile AR. They found interactions with color and luminance on depth perception.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They found that the richer geometry cues provided by the icosahedron and apple positively influenced reaching and grasping behaviors. In a similar manner, Do et al [15] evaluated the effect of object color and luminance on objects of different shapes for depth judgments in mobile AR. They found interactions with color and luminance on depth perception.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, an anchoring shadow may be more sensitive to mismatches between the contours of a shadow and its associated object [11,37]. However, as noted in Do et al [15], AR depth perception experiments rarely incorporate multiple object shapes. Accordingly, in their mobile AR study they evaluated how color and luminance interacted to affect depth perception across four objects: a cube, a sphere, the Stanford bunny, and a low polygon version of the Stanford bunny.…”
Section: Shape and Shadows In Xrmentioning
confidence: 98%
See 1 more Smart Citation
“…Previously, a global positioning system was mainly utilized to implement geo-based mixed reality games in the early twentieth century. However, more recently, computer vision, deep learning, and big data analytics are great tools for estimating the poses and giving geolocation data to process in the games accurately and quickly [20]. Therefore, for achieving the advancement of these tools, the purpose of geolocation mixed reality games for research should be first encouraged to allow a period of trial and error, even though the research purpose of gaming may not directly and significantly relate to the increasing market trend and popularity of games, in the long run, comparing to the commercial purpose gaming, according to our investigation.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…Although the current implementation was done on an iPad Pro (to make use of its LiDAR), the concepts could be readily exported to the head-mounted displays currently supported by Unity and Unity MARS. In that case, sensor requirements would need to be met, and issues such as outdoor luminance levels that may hinder perception [11], ocular vergence-accommodation conflicts [48,64] and latency issues leading to visually induced motion sickness [4] have to be considered. Sensor requirements vary between concepts according to complexity, as shown in Table 1.…”
Section: Limitations and Future Workmentioning
confidence: 99%